Chaos synchronization of logistics, Qi and Maxwell-Bloch systems for chaos-based communication - Abdul Fataf, Nur Aisyah (2018)
Since chaos synchronization has become a very important topic regarding applications in communication, various different communication schemes have been proposed by many researchers. In most of the cases, chaos based communication research are based on synchronization of chaotic systems. The signal at the transmitter and receiver are synchronized in order to use the output in communication model. In this thesis, we investigate chaos based communication by using non-synchronized states of chaotic/hyperchaotic systems. The message can be transmitted even if the transmitter and the receiver are in non-synchronized states. At the beginning of the thesis, we investigate the synchronization between discrete chaotic systems using techniques of nonlinear controller. The choice of the technique is due to the effectiveness of the synchronization scheme in terms of time and error. After achieving synchronization, we then apply the method for communication. We implement the chaotic masking communication scheme technique to demonstrate the effectiveness of the proposed scheme. In the next part, we examine an adaptive synchronization of hyperchaotic Qi-System by using nonlinear controller. Based on the analysis, the system loses its information during the synchronization due to the effect of the nonlinear controller. Besides, the complexity also decreases from a single system to the coupled systems. Hence, we propose and redefine the chaotic masking scheme with non-synchronized coupled systems for communication. The analysis shows that the proposed scheme is successfully implemented and very robust.Finally, we explore the dynamics of a 5D model governed by the Maxwell-Bloch equations and investigate the synchronization of the systems by using unidirectional linear coupling. We also identify the non-synchronized region and utilize the region to implement a new communication scheme by using chaos shift key technique. The analysis shows the effectiveness of the proposed scheme.